Altered Functional Brain Network in Systemic Lupus Erythematosus Patients Without Overt Neuropsychiatric Symptoms Based on Resting-State Functional Magnetic Resonance Imaging and Multivariate Pattern Analysis - Wang, Yiling; Jiang, Muliang; Huang, Lixuan; Meng, Xia; Li, Shu; Pang, Xiaoqi; Zeng, Zisan (Frontiers in Neurology, 2021)
Objective: This study aims to investigate the alterations in functional brain network in systemic lupus erythematosus patients without overt neuropsychiatric symptoms (non-NPSLE) from the perspective of degree centrality (DC) and functional connectivity (FC) using resting-state functional magnetic resonance imaging (rs-fMRI) and multivariate pattern analysis (MVPA) approach. Methods: DC analysis was performed based on the rs-fMRI data derived from 47 non-NPSLE patients and 47 healthy controls (HCs). Nodes with abnormal DC were utilized as seeds for further FC analysis. The correlation between MRI variables and clinical or neuropsychological data were analyzed using Pearson correlation analysis. Finally, MVPA classification based on DC was performed. Results: When compared with the HCs, the non-NPSLE patients exhibited remarkably higher DC in the bilateral hippocampus (HIP), right insula (INS), and lower DC in the left superior parietal gyrus (SPG). Furthermore, the patients displayed significantly higher FC between the left HIP and the left INS/left dorsolateral middle frontal gyrus (MFGdor)/left supramarginal gyrus (SMG) and higher FC between the right HIP and the right middle temporal gyrus/right MFGdor/right dorsolateral inferior frontal gyrus/right SMG (all aforementioned imaging variables underwent cluster-level false discovery rate corrections, the voxel threshold was p<0.001, cluster threshold was p<0.05). Correlation analysis revealed significantly negative correlations between DC values of the right INS and disease activity, and the DC values of the right HIP and the MoCA scores. The accuracy, sensitivity and specificity of MVPA classification based on DC were 72.34%, 63.83%, and 80.85%, respectively. The most discriminative power brain regions were chiefly located within the temporal, parietal and frontal regions. Conclusion: Patients with non-NPSLE exhibited abnormal DC and FC in the brain network. MVPA based on DC possessed commendable classification ability. Our study may provide a novel perspective on the neuropathological mechanisms underlying subclinical brain damage in non-NPSLE.